Implementation of Yoga as a Holistic Intervention Strategy to Improve Cognitive and Motor Function in the Elderly: Literature Review - Ikadarny (Journal Physical Health Recreation (JPHR), 2025)
The natural process of aging is characterized by a decline in cognitive and motor functions, which impacts the quality of life of older adults. Yoga and other non-pharmacological therapies have shown promising results in maintaining and improving these abilities. As a comprehensive intervention approach, yoga not only improves motor skills but also influences cognition through meditation, breathing exercises, and mental focus. As a result, yoga falls into the category of holistic intervention techniques that are ideal for older adults. The purpose of this article is to review scientific research on the benefits of yoga as a comprehensive intervention strategy to improve cognitive and motor functions of older adults. A systematic review of several empirical studies and related literature was the methodology used. According to the findings, frequent yoga practice can improve balance, flexibility, executive function, and general quality of life of older adults. Therefore, yoga can be viewed as a preventive and restorative strategy in the field of geriatric care.